Antenatal screenings and maternal diagnosis among pregnant women in Sao Tome & Principe-Missed opportunities to improve neonatal health: A hospital-based study - Alexandra Vasconcelos; Swasilanne Sousa; Nelson Bandeira; Marta Alves; Ana Luísa Papoila; Filomena Pereira; Maria Céu Machado (Public Library of Science (PLoS), 2022)
Newborn mortality and adverse birth outcomes (ABOs) in Sao Tome & Príncipe (STP) are overwhelmingly high, and access to quality-antenatal care (ANC) is one of the strategies to tackle it. This study aimed to fill the gaps in ANC screenings with a focus on how to improve neonatal outcomes. We conducted a retrospective hospital-based study in which ANC pregnancy cards were reviewed. Screenings were described and compared according to the total number of ANC contacts: 1-3 (inadequate), 4-7 (adequate), and ≥8 (complete). The collected data were entered into QuickTapSurvey and exported to SPSS version 25 for analysis. Statistical significance was considered at a p-value ≤0.05. A total of 511 ANC pregnancy cards were reviewed. Mothers' mean age was 26.6 (SD = 7.1), 51.7% had a first trimester early booking, 14.9% (76) had 1-3 ANC contacts, 46.4% (237) had 4-7 and 38.7% (198) ≥8. Screening absence was found in 24%-41%, lack of money was registered in 36%. Pregnant women had no screening performed for HIV in 4.5%, syphilis in 8.8%, HBV 39.3%, malaria 25.8%, hemoglobin 24.5%, blood glucose 45.4%, urine 29.7%, stool exams 27.8% and 41.1% had no ultrasound. Screening completion for blood group, HIV, malaria, urine, hemoglobin, and coproparasitological exam were found to have a statistically significant difference (p<0.001) for the complete ANC group when compared to other groups. Antenatal problems identified were: 1) bacteriuria (43.2%); 2) maternal anemia (37%); 3) intestinal parasitic infections (59.2%); 4) sickle cell solubility test positive (13%); and 5) a RhD-negative phenotype (5.8%). Missed-ANC treatments were up to 50%. This study reveals a coverage-quality gap in STP since no pregnant woman is left without ANC contact, although most still miss evidence-based screenings with an impact on neonatal outcomes. Strategies such as implementing a total free ANC screening package in STP would enhance maternal diagnosis and prompt treatments.